FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT IBU TERHADAP KELENGKAPAN IMUNISASI PADA BAYI USIA 9-12 BULAN DI DAERAH RAWA BOKOR KOTA TANGERANG - Fisnanda Fisnanda (Nusantara Hasana Journal, 2022)
The global Covid-19 pandemic has greatly affected not only the economy, but also in various sectors. One of them that is affected is all health services, especially basic health services, such as immunization services. The decline in the number of complete and advanced routine basic immunization coverage was also affected by the COVID-19 pandemic. The burden of disease that should be prevented through immunization (PD3I) is still very high in Indonesia. The influencing factors are education, work, attitude, family support, and affordability of access to services. The research method used is this type of research using observational analytic with a retrospective approach. The sampling technique used is Simple Random Sampling. The number of samples in this study were 81 respondents. Bivariate analysis using chi-square test and multivariate analysis using logistic regression analysis. The results of the study of 81 respondents showed that the level of education had a value (p = 0.054; OR 3.802), employment status (p = 0.012; OR 0.225), mother's attitude (p = 0.052; OR 0.321), family support (p = 0.057; OR 0.295), and affordability of access (p=0.004; OR 5.964). The conclusion of this study is that there is an influence between employment status and access to affordability with mother's interest in completeness of immunization in the Rawa Bokor area, Tangerang City.